Stratification of Factors Determining the Effectiveness of Antibacterial Therapy of Wound Defects in Diabetic Foot Syndrome - T. N. Kuzmina; N. V. Rogova (Антибиотики и Химиотерапия, 2020)
The article identifies and analyzes the factors determining the effectiveness of antibacterial therapy of wound defects in patients with diabetic foot syndrome. Sensitivity to antibiotics and the nature of microflora of the strains received from patients with diabetic foot syndrome were studied. It was established that patients with diabetic foot syndrome in Volgograd suffered chronic infectious processes. The authors give recommendations for improving the provision of medical care to patients with diabetic foot syndrome based on the results obtained.